Identification of gut contents and microscopical observations of the gut epithelium of the macrophagous ascidian Cibacapsa gulosa Monniot and Monniot 1983 (Phlebobranchia, Octacnemidae) - Lescano, María Natalia; Fuentes, V. L.; Sahade, Ricardo Jose; Tatian, Marcos (Polar Biology)
Octacnemids represent a different pathway in the evolution of the typical filter-feeding ascidians. We examine and identify the prey items in the gut contents and describe the cell types that constitute the inner wall of different sections of the gut of the macrophagous octacnemid Cibacapsa gulosa collected in the South Sandwich Islands, Antarctica. A great variety of prey items were found: polychaetes, copepods, halacarids, amphipods, isopods and ophiurids. The internal wall of the gut is lined with a monostratified, prismatic epithelium. Different cell types occur in the inner wall in different sections. The presence of zymogenic cells throughout the internal gut epithelium, as well as the presence of concretion cells in the stomach of C. gulosa, also present in the macrophagous tunicate group Sorberacea ( = Hexacrobylidae), can be considered an adaptation to the macrophagous diet. Fil: Lescano, María Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina Fil: Fuentes, V. L. Instituto de Ciencias del Mar. Departamento de Biología Marina y Oceanografía; España Fil: Sahade, Ricardo Jose. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto de Diversidad y Ecología Animal; Argentina Fil: Tatian, Marcos. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto de Diversidad y Ecología Animal; Argentina